Potentiation of [DELTA]F508- and G551D-CFTR-Mediated Cl.sup.- Current by Novel Hydroxypyrazolines - Park, Jinhong; Khloya, Poonam; Seo, Yohan; Kumar, Satish; Lee, Ho K; Jeon, Dong-Kyu; Jo, Sungwoo; Sharma, Pawan K; Namkung, Wan (PloS one, 2016)
The most common mutation of CFTR, affecting approximately 90% of CF patients, is a deletion of phenylalanine at position 508 (F508del, [DELTA]F508). Misfolding of [DELTA]F508-CFTR impairs both its trafficking to the plasma membrane and its chloride channel activity. To identify small molecules that can restore channel activity of [DELTA]F508-CFTR, we synthesized and evaluated eighteen novel hydroxypyrazoline analogues as CFTR potentiators. To elucidate potentiation activities of hydroxypyrazolines for [DELTA]F508-CFTR, CFTR activity was measured using a halide-sensitive YFP assay, Ussing chamber assay and patch-clamp technique. Compounds 7p, 7q and 7r exhibited excellent potentiation with EC.sub.50 value <10 [mu]M. Among the compounds, 7q (a novel CFTR potentiator, CP7q) showed the highest potentiation activity with EC.sub.50 values of 0.88 ± 0.11 and 4.45 ± 0.31 [mu]M for wild-type and [DELTA]F508-CFTR, respectively. In addition, CP7q significantly potentiated chloride conductance of G551D-CFTR, a CFTR gating mutant; its maximal potentiation activity was 1.9 fold higher than the well-known CFTR potentiator genistein. Combination treatment with CP7q and VX-809, a corrector of [DELTA]F508-CFTR, significantly enhanced functional rescue of [DELTA]F508-CFTR compared with VX-809 alone. CP7q did not alter the cytosolic cAMP level and showed no cytotoxicity at the concentration showing maximum efficacy. The hydroxypyrazolines may be potential development candidates for drug therapy of cystic fibrosis.